Super‐Resolution Spatial Proximity Detection with Proximity‐PAINT. Issue 2 (9th November 2020) - Schueder, Florian; Lara‐Gutiérrez, Juanita; Haas, Daniel; Beckwith, Kai Sandvold; Yin, Peng; Ellenberg, Jan; Jungmann, Ralf
Abstract: Visualizing the functional interactions of biomolecules such as proteins and nucleic acids is key to understanding cellular life on the molecular scale. Spatial proximity is often used as a proxy for the direct interaction of biomolecules. However, current techniques to visualize spatial proximity are either limited by spatial resolution, dynamic range, or lack of single‐molecule sensitivity. Here, we introduce Proximity‐PAINT (pPAINT), a variation of the super‐resolution microscopy technique DNA‐PAINT. pPAINT uses a split‐docking‐site configuration to detect spatial proximity with high sensitivity, low false‐positive rates, and tunable detection distances. We benchmark and optimize pPAINT using designer DNA nanostructures and demonstrate its cellular applicability by visualizing the spatial proximity of alpha‐ and beta‐tubulin in microtubules using super‐resolution detection. Abstract : A modified implementation of DNA‐PAINT microscopy is used to detect spatial proximity of biomolecules with super‐resolution capabilities. The new technique, called Proximity‐PAINT, features a precisely tunable detection range, high sensitivity and low false‐positive rates. The implementation can be applied to visualize cellular protein‐protein interactions and other biomolecules of interest, such as nucleic acids.